Business model adaptation in response to an exogenous shock: An empirical analysis of the Portuguese footwear industry. (11th May 2018) - Corbo, Leonardo; Pirolo, Luca; Rodrigues, Vasco
Business models have received increasing attention in both academic and managerial communities. However, little attention has been paid to how business models change in response to extreme events. This topic is of critical importance since failure to achieve adaptation in a timely manner can lead to negative consequences such as a significant decrease in firm value or bankruptcy. This study explores how the business model paradigm of the Portuguese footwear industry changed following China's entry into the World Trade Organization in 2001. The empirical results suggest that the shock acted as a trigger for change for the Portuguese footwear firms which reflected in the adoption of a new business model characterized by speed and flexibility in the manufacturing process, faster response to customer needs and, in specific cases, in downward integration through the creation of own brands selling directly to final consumers. This result, however, was not the outcome of a sudden change but rather the consequence of a planned adaptation strategy led by a key industry actor that acted as a network orchestrator coordinating the actions of the Portuguese footwear firms. The implications of these findings as well as directions for future research are discussed in the last part of this study.